Perbandingan Hasil Belajar Siswa Terkait Keefektifan Penggunakan Media Pembelajaran Pada Materi Kegiatan Ekonomi - Fransiska Yunita Litau; Kristin Sinisuka; Rindang Nur Rezeki Sitorus; Syahrial Syahrial (Lembaga Pengembangan Kinerja Dosen, 2024)
Economic activity is a complex as well as integral phenomenon in the life of modern citizens. This abstract explores various aspects of economic activity, including the process of production, distribution, and consumption of an object or service. Through micro and macroeconomic analysis, this abstract investigates the attitudes of economic actors, market interactions and the consequences of economic policies on the development and welfare of citizens. Not only that, this abstract also examines the position of technology, globalization, and facts.